Inovasi Produk Fintech Syariah dalam Mendorong Inklusi Keuangan di Indonesia - Eman Suherman; Iwan Setiawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The development of digital technology has encouraged the transformation of the financial sector through the emergence of Sharia financial technology (fintech) as a financial service based on Islamic principles that emphasize justice, transparency, and public benefit (maslahah). The presence of various Sharia fintech products such as Sharia peer-to-peer (P2P) lending, Sharia crowdfunding, Sharia E-wallets, and digital ZISWAF (zakat, infaq, alms, and waqf) services is considered capable of increasing financial inclusion in Indonesia, especially for unbanked communities and MSMEs that have limited access to formal financial services. This study aims to analyze the innovation of Sharia fintech products, their role in increasing financial inclusion, and their conformity with the perspective of Islamic Economic Law. This research uses a qualitative method with a library research approach through collecting data from scientific journals, DSN-MUI fatwas, OJK and Bank Indonesia regulations, as well as various literature related to Sharia fintech published within the last five years. The data analysis technique was carried out descriptively and analytically by examining the concepts, implementation, and regulations of Sharia fintech in Indonesia. The results of the study indicate that Sharia fintech has a strategic role in expanding public access to financial services through the digitalization of financing, payments, and Islamic social fund collection. In addition to increasing Islamic financial inclusion and literacy, Sharia fintech also helps reduce transaction costs, facilitate MSME financing access, and expand the distribution of financial services to remote areas. From a Sharia perspective, the operation of Sharia fintech must continue to adhere to DSN-MUI fatwas and maqashid sharia principles in order to avoid elements of riba, gharar, and maisir and to create justice and public benefit for society. Therefore, Sharia fintech has a great opportunity to support the development of an inclusive and sustainable Islamic digital economy in Indonesia, although strengthening regulations, Sharia supervision, public education, and product innovation based on community needs are still required.